The philosophy of tacit knowledge : the tacit side of knowledge management in organizations - Johannessen, Jon-Arild (Emerald points, 2022)
Knowledge management expert Jon-Arild Johannessen presents a comprehensive exploration of tacit knowledge based on the research problem: How can tacit knowledge be used to improve organizational performance in practice?